Black theology versus black spirituality and black faith: The centrality of spirituality and faith in black theology of liberation in the South African context - Buffel, O. A. (HTS teologiese studies, 2021)
Black theology, which is linked to black power in the context of the United States of America and black consciousness in the context of South Africa is often regarded as having nothing to do with spirituality, faith and salvation. It is often regarded by critics as radical, militant and political. In some circles its theological character is questioned. Advocates of liberation theology, past and present are accused of mixing religion with politics. The article traces the history of black theology, as part of liberation theology, which started in the 1960s in three contexts, namely Latin America, United States of America and South Africa. The article argues that spirituality, faith and salvation are central to black theology of liberation. The critical theological reflection that black theology of liberation is all about happens in the context of the spiritual journey of the poor believer and oppressed.Contribution: The contribution that this article makes is to serve as a corrective discourse that rebuts the mistaken accusation that black liberation theology has nothing to do with spirituality and faith. The article makes a direct link between spirituality and faith on the one hand and on the other hand liberating Christian praxis of the poor in their spiritual journey, in the context of South Africans as they struggle to liberate themselves amid poverty, service delivery struggles and COVID-19 and its implications.